Differences in maximum oxygen consumption of football players of different positions in the team - Ivanek, V.; Dukic, B.; Mikic, B.; Mirkovic, M.; Rezic, M. (Acta Kinesiologica, 2021)
The aim of this research is to determine the differences between the aerobic functional abilities of football players from different positions in the team, which should serve as a starting point in planning and monitoring the training process of football players. VO2max, as a basic parameter of functional abilities, was obtained by applying a laboratory progressive test on the treadmill.The sample of respondents was composed of 57 respondents (GOD = 22.47 ± 3.78SD), football players of clubs competing in the first and second leagues of Serbia from the area of Vojvodina, of which 8 goalkeepers, 16 defensive, 17 midfielders and 16 attackers.To test the functional capabilities (oxygen consumption -VOmax), we used a test of progressive continuous load on the treadmill with increasing load per minute through a "breath-by-breath" gas analyzer (Quark PFT ErgoCPET, Cosmed, Italy), which gave data on ventilation and spiroergometric parameters of the subjects by different positions in the team. Anthropometric measures of body weight-(TM) and body height-(TV) were applied to test the morphological characteristics of the subjects.SPSS 20.0 software package was used for data processing. In order to determine the statistically significant differences of the measured variables between football players by positions, a one-factor anova of different groups, the level of statistical significance (p <0.05) was used.The obtained results of maximum oxygen consumption indicated that there is a statistically significant difference in aerobic abilities between goalkeepers and players in other positions, and they are certainly a consequence of the physiological requirements placed before them and the different training process.The highest mean value of VO2 max had midfielders (53.3 ± 1.9 ml / kg / min), followed by attackers (52.9 ± 4.4 ml / kg / min), defensive players (51.8 ± 3, 3 ml / kg / min) while the lowest values were recorded in the goalkeeper (50.5 ± 1.8 ml / kg / min). There is a logical conclusion that the need for running midfielders is the greatest, and the goalkeeper the least, and that the results are the result of training processes and different requirements for individual positions in the team.Key words:football, VO2 max, maximum oxygen consumption, aerobic capacity